2017
DOI: 10.1049/iet-map.2017.0060
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid non‐uniform‐ Q lossy filters with substrate integrated waveguide and microstrip resonators

Abstract: Three lossy filters with flat passband are proposed with substrate integrated waveguide (SIW) and microstrip resonators, designed with the non‐uniform‐Q method. By properly selecting the lower‐Q‐to‐higher‐Q ratio, the 0.2 dB bandwidth of the first filter is obtained to be 215 MHz (17% improvement), which is equivalent to a uniform unloaded Q‐factor of 820 at the cost of additional in‐band insertion loss (IL) of 0.5 dB, when compared with the full‐SIW filters. Further, two techniques are utilised to adjust the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Although the center frequency shifts to the lower side at about 4 MHz, it is found that the measured S-parameters are in good agreement with those from EM simulation. It is found that the advantages of the proposed BPF are flexibly controllable unloaded quality factor and good flatness in the passband compared with other references [14,15,16,21,26,27,28,29,30,31,32].…”
Section: Design Of Fourth-order Bpf With Flat Passbandmentioning
confidence: 89%
“…Although the center frequency shifts to the lower side at about 4 MHz, it is found that the measured S-parameters are in good agreement with those from EM simulation. It is found that the advantages of the proposed BPF are flexibly controllable unloaded quality factor and good flatness in the passband compared with other references [14,15,16,21,26,27,28,29,30,31,32].…”
Section: Design Of Fourth-order Bpf With Flat Passbandmentioning
confidence: 89%
“…For this SIWbased high-pass filter, the cut-off wavelength (λ c , hpf ) is found by ( 1) and (2) as 28.61 mm. The cut-off frequency and wavelength of the substrate integrated waveguide [14]:…”
Section: A Step 1: the Design Of The Conventional Siw-based High-pass...mentioning
confidence: 99%
“…Besides, sub-mode SIW resonators are not as flexible and convenient as the MSL ones in developing higher-order BPFs. In this event, some researchers have proposed the hybrid SIW and MSL BPFs with outstanding performance [19][20][21][22][23][24][25][26]. In Ref.…”
mentioning
confidence: 99%
“…In Ref. [22], a series of fourth-order non-uniform-Q lossy BPFs with SIW and microstrip structures are proposed to achieve improved passband flatness and compact physical footprint. In Refs [23][24][25][26], quarter-wavelength (λ/4) short-circuited MSLs are connected to the normal full-mode SIW or sub-mode SIW cavities directly.…”
mentioning
confidence: 99%